Body Mass Index Conditions of Running Athletes Before Ramadan - Arief Ibnu Haryanto; Ardin Abdul Gani; Gilang Ramadan; Giofandi Samin; Iwan Fataha; Sulasikin Sahdi Kadir (STKIP Muhammadiyah Kuningan, 2022)
This study aims to determine the condition of the body mass index of athletes running in Gorontalo. The research method used is ex-post facto descriptive with a research sample of 18 athletes, consisting of 15 male athletes and three female athletes. This study uses the Body Mass Index instrument by measuring the athlete's height and weight. Data analysis using Benchmark Reference Assessment (PAP), then the data is processed using ms. Excel. This study revealed that all athletes in Gorontalo City with 100% male and female athletes have an average Body Mass Index. This study illustrates that the trainer maximized the exercise pattern and the nutritional practice to keep the Body Mass Index regular. However, coaches must continue to monitor their athletes to always have an average Body Mass Index, especially during Ramadan.